IMPLEMENTASI KEBIJAKAN PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN ROKAN HILIR PROVINSI RIAU - Febri Yuliani (Indonesian Journal of Dialectics, 2011)
This study attempted to identify, explore, uncover and analyze the answers to the research question “Why the policy implementation of policies controlling land and forest fires in Rokan Hilir regency of Rokan Hilir district failed to make free forest and land fires?” Seeing the complexity of problems encountered, then with through qualitative research design and descriptive methods, is expected to achieve the research objectives, namely (one) To examine and analyze the implementation of policies in an effort to control forest and land fires in Rokan Hilir regency. (2) To assess and analyze the factors that play a role in the implementation of policies controlling land and forest fires in Rokan Hilir (3) To improve or discover new concepts regarding the implementation of policies controlling land and forest fires. The results showed that: The successful implementation of policies determined by the factors: the basic measures and policy objectives, the sources of policy, the communication between the organization and implementation activities, characteristic of executing agencies, the economic, social and political and trends of implementing.